2008
DOI: 10.1364/oe.16.010315
|View full text |Cite
|
Sign up to set email alerts
|

Cavity resonances of metal-dielectric-metal nanoantennas

Abstract: We propose a new design of optical nanoantennas and numerically study their optical properties. The nanoantennas are composed of two cylindrical metal nanorods stacked vertically with a circular dielectric disk spacer. Simulation results show that when the dielectric disk is less than 5nm in thickness, such nanoantennas exhibit two types of resonances: one corresponding to antenna resonance, the other corresponding to cavity resonances. The antenna resonance generates a peak in scattering spectra, while the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The behavior predicted for the latter is similar to that for spherical particles, with a set of bonding modes that strongly red-shift with narrowing gaps and that determine both the near-and the far-field response. 17 In contrast, for the corresponding flat-gap antennas, we found two different sets of modes, 20,21,84 longitudinal antenna plasmons and transverse cavity plasmons, which behave in fundamentally different ways. The LAPs dominate the far-field response and saturate spectrally for narrow gaps.…”
Section: ■ Summary and Discussionmentioning
confidence: 64%
“…The behavior predicted for the latter is similar to that for spherical particles, with a set of bonding modes that strongly red-shift with narrowing gaps and that determine both the near-and the far-field response. 17 In contrast, for the corresponding flat-gap antennas, we found two different sets of modes, 20,21,84 longitudinal antenna plasmons and transverse cavity plasmons, which behave in fundamentally different ways. The LAPs dominate the far-field response and saturate spectrally for narrow gaps.…”
Section: ■ Summary and Discussionmentioning
confidence: 64%
“…Numerous studies have demonstrated that well-designed metallic nanostructures exhibit excellent performances as optical nanoantennae, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] plasmonic nanocavities, and sub-wavelength waveguides. [19][20][21][22][23] Metal nanoparticles, [1][2][3] monopole and dipole metal nanorods, [4,5] multipole metal nanocrescents and nanorings: [6][7][8] all of these examples have strong surface plasmon resonance and could be employed as optical nanoantennae to efficiently interconvert the propagating radiation and confined local fields, which have been applied in surface-enhanced raman scattering (SERS), [24][25][26] sensing, and nanospectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These ideas have guided the efficient design of metasurfaces 6,7 and the modelling of a variety of composite nanostructures, including plasmonic NP clusters [8][9][10] , NP rings exhibiting strong optical magnetism 11 and microcavity lasers 12 . However, the direct application of these concepts to photonic circuits has so far been limited to modelling and tuning optical nanoantennas [13][14][15][16][17][18][19] , and to realizing a ladder network of two-dimensional (2D) nanoinductors and nanocapacitors in the form of a subwavelength grating at mid-infrared frequencies 4 . These earlier experiments have demonstrated nanocircuits with limited complexity and specific symmetry constraints.…”
mentioning
confidence: 99%